FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KEPATUHAN TENAGA KESEHATAN MELAKUKAN CUCI TANGAN (STUDI KASUS DI INSTALASI RAWAT INAP RAJAWALI RSUP DR. KARIADI SEMARANG) - Amalia, Rizka; Widagdo, Laksmono; BM, Syamsulhuda (Fakultas Kesehatan Masyarakat, 2016)
Disobedience of health care workers to practice hand hygiene often related with the incidence of nosocomial infection in hospital. Nosocomial infection rates in Rajawali Inpatient Installation of RSUP Dr. Kariadi Semarang is 24,4 permile and including one of high rates in RSUP Dr. Kariadi areas. Obedience rate of health care workers on October 2014 is 48,2% which is far away from achievement target 100%. This research will aims to analyzing correlation factors with obedience level of health care workers to practice hand hygiene in Rajawali Inpatient Installation of RSUP Dr. Kariadi Semarang. This research is a quantitative research with cross-sectional approach. Respondents of this research is 70 health care workers in Rajawali Inpatient Installation of RSUP Dr. Kariadi Semarang. The sampling technique using simple random sampling. Research result shows 60% of respondents was disobedience to practice hand hygiene according to procedure. Statistic analyze with Chi Square Test showed that variables correlated with obedience level of health care workers to practice hand hygiene are knowledge of respondents (p-value= 0,035) and attitude of respondents (p-value= 0,035). Other factors that not correlated with obedience level of health care workers to practice hand hygiene are age of respondents (p-value= 0,308), education level of respondents (p-value= 0,136), work period of respondents (p-value= 1,000), facilities (p-value= 1,000), hand hygiene socialization (p-value= 0,342), regulation (p-value= 1,000), supervision (p-value= 0,148), peer support (p-value= 0,514) due to have p value > 0,05. Necessary hand hygiene training routinely and regulations that offset the sanctions for disobedience of health care workers to practice hand hygiene according to procedure.